Rapid assessment of distribution network equipment status based on fuzzy decision making - Qian, Wang; Yuquan, Li; Xiaohui, Wang; Kun, Yang; Yang, Liu; Zhongyuan, Xia; Guangyu, Lan; Yunlong, Liu; Jiyuan, Tang (Frontiers in Energy Research, 2024)
Voltage instability, power imbalance, and unreliability are caused mainly by equipment failure in the distribution system. However, it is challenging to detect equipment failures at an early stage. To address these issues, we propose a fast evaluation method for the state of electrical distribution equipment based on fuzzy decision-making. Firstly, key indices are selected from the multi-source equipment information. However, the traditional XGBoost algorithm is unsuitable because some indices are incompetent to quantify. Therefore, this paper constructs the mapping between key indices and equipment status scores by combining the fuzzy iterative method and the XGBoost algorithm. This method shows better accuracy compared with traditional methods. Lastly, the proposed assessment model is confirmed by using the distribution transformers as an example. The result shows that the proposed multi-source information assessment method can quickly and accurately determine the operation status of electrical distribution equipment